Online Purchase Intention of Digital Products among University Students - Lim, Lee Ping; Ong, Choon Hee; Teo, Poh Chuin; Theresa, Ho Char Fei (Business Management and Strategy, 2024)
Online shopping is one of the e-commerce platforms. It has gradually become famous worldwide and is expanding quickly in nations because of its continuous changes and upgrades. Most online shoppers are aged 20 and 30. University students have become one of Malaysia's most significant market populations due to the growth of digital educational services. However, it is still unclear what factors drive these university students toward online purchase of digital products. This study examines the relationship between social influence, product preference, system security, perceived pricing, and online purchase intention of digital products among public university students. 227 undergraduate students enrolled in Malaysian public universities were surveyed using a quantitative questionnaire. The Statistical Package for Social Science (SPSS) was used to analyze the collected data for this project. The findings of this study demonstrated significant relationships between online purchase intention and social influence, system security, and perceived pricing. According to the analysis results, perceived pricing has the most significant influence on purchasers' intention to purchase online. Hence, service providers should ensure that their product pricing is reasonable and worth the money to purchase. Additionally, marketing strategies can be tailored using e-WOM practices to raise social influence, and the system's security aspects must be enhanced to increase trust and knowledge of the legitimacy of online purchases.